A Simple μ-PTV Setup to Estimate Single-Particle Charge of Triboelectrically Charged Particles - Landauer, Johann; Tauwald, Sandra Melina; Foerst, Petra (Frontiers in Chemistry, 2019)
Triboelectric separation is a useful phenomenon that can be used to separate fine powders. To design technical devices or evaluate the potential of powders to be triboelectrically separated, knowledge about the charge distribution on a single-particle level has to be obtained. To measure the single-particle charge distribution in an application-oriented way, a simple $μ$-PTV system was developed. The designed setup consists of a dispersing and charging unit using a Venturi nozzle and a tube, respectively, followed by a separation chamber. In the separation chamber, a homogenous electrical field leads to a deflection of the according their individual charge. The path lines of the particles are captured on single frames using microscope optics and a high-speed camera with a defined exposure time. The particles are illuminated using a laser beam combined with a cylindrical lens. The captured pictures enable simultaneous measurement of positively and negatively charged particles. Initial experiments were carried out using starches of different botanical origins and protein powder. Single-component experiments with starch powders show completely different charge distributions for positively and negatively charged particles, whereas protein powder shows bipolar charging. Different starch-protein mixtures each show similar patterns for positive and negative charge distributions.